STRUCTURAL AND ELECTRONIC PROPERTIES OF TRANSITION METAL DI-CHALCOGENIDES (MX2) M=(Mo, W) AND X=(S, Se) IN BULK STATE: A FIRST-PRINCIPLES STUDY (Journal of Institute of Science and Technology, 2017)
Transition metal di-chalcogenides (MX2) M=(Mo, W) and X=(S, Se) in bulk state are of great interest due to their diverse applications in the field of modern technology as well as to understand the fundamental aspect of Physics. We performed structural and electronic properties of selected systems using density functional theory implemented in Tight Binding Linear Muffin- tin Orbital (TBLMTO) approach with subsequent refinement. The structural optimization is performed through energy minimization process and lattice parameters of optimized structures for MoS2, MoSe2, WS2 and WSe2 are found to be 3.20Å, 3.34Å, 3.27Å and 3.34Å respectively, which are within the error bar less than 5% with experimental values. The band gaps for all TMDCs are found to be of indirect types with semiconducting behaviours. The values of band gap of MoS2, MoSe2, WS2 and WSe2 in bulk state are found to be 1.16eV, 108eV, 1.50eV and 1.29eV respectively which are comparable with experimental and previously calculated data. Due to the symmetric nature of up spin and down spin channels of Density of States (DOS) all the systems selected are found to be non magnetic. However it fully supports the results obtained from band structure calculations. The potential and charge distributions plots support the results. The charge density plots reveals the covalent nature of bond in (100) plane. However (110) plane shows mixed types of bonding.Journal of Institute of Science and TechnologyVolume 22, Issue 1, July 2017, page: 41-50